THE RELATIONSHIP OF FAMILY SUPPORT WITH PREVENTIVE BEHAVIOR DM COMPLICATION (DIABETES MELLITUS) (STUDIED IN THE VILLAGE OF MANCAR DISTRICT OF PETERONGAN JOMBANG REGENCY) - Ivo Arga Adinata; Hindyah Ike; . Anita (Jurnal Keperawatan, 2013)
Diabetes Mellitus is metabolic and degenerative disease that is currently so feared by many people. DiabetesMellitus is on of non-communicable diseases which has become a public health problem, no only in Indonesia butalso in the world. The purposes of this research was to know the relationship of family support with preventivebehavior of Diabetes Mellitus in the village of Mancar district of Peterongan Jombang regency. This researchdesign was analitic cross sectional. The populations were all sufferers of Diabetes Mellitus in the village ofMancar district of Peterongan Jombang regency in 2013 was amounted 37 people. The sample was 34 people.Sampling technique used was sample random sampling. The variable in this research consisted of independentvariable that’s the family support and dependent variable that’s preventive behavior of diabetes mellituscomplication. The research instrument used was a questionnaire with data processing by editing, coding, scoring,tabulating and statistic test used chi square. The results showed that’s almost entirely family support was negativewith total 26 respondents (76,5%), majority preventive behavior of diabetes mellitus complication was negativeamounted 21 respondents (61,8%). The test of chi square showed that the significant value of  = 0,001 < (0,05), so H1 accepted. The conclusion there is relation of family support with preventive behavior of DiabetesMellitus complication in the village of Mancar district of Peterongan Jombang regency.